Dynamics of self-assembly in complex fluids - Gonnella, G; Orlandini, E; Yeomans, J (1998)
Lattice Boltzmann simulations are used to study the phase ordering of a system quenched into a lamellar phase. Hydrodynamic modes are found to be essential for the fluid to avoid frozen metastable configurations and reach the equilibrium state. We also show that a shear imposed on an equilibrium array of droplets can induce a micellar-lamellar transition.